Organizational Management Disasters During the Anti Japanese War: A study on the Negative Impact of the "Wang-Kang Directive" on the Northeast United Resistance Army - Zhao, Liang (International Journal of Multidisciplinary Research, 2026)
This paper examines the multifaceted negative impact of the “Wang-Kang Directive” (the June 3, 1936, “Secret Letter to the Comrades in Charge of Eastern Manchuria”) on the operations and cohesion of the Northeast United Resistance Army (NURA). While acknowledging the directive’s intended role in broadening the anti-Japanese united front by combating “Leftist” closed-doorism, the analysis focuses on its profound internal contradictions and their detrimental consequences. It argues that the directive’s core problematic tenets—including the passive strategic concept of “awaiting the major turn of events,” the politically compromising injunction to “not couple anti-Manchukuo with anti-Japanese,” and a grave misjudgment of the Japanese-puppet “collective hamletization” policy — collectively acted as a debilitating force on the NURA. These errors, emanating from a center remote from the Manchurian battlefield, induced strategic confusion, undermined effective political mobilization, and critically fractured organizational unity during a period of intense Japanese military pressure. The case of Commander Zhao Shangzhi’s vehement criticism and subsequent political suppression is presented as a pivotal illustration of the directive’s role in catalyzing destructive internal strife, which silenced pragmatic frontline expertise and weakened the NURA’s leadership.